Metode Yanbu’a Sebagai Pedoman Membaca Al-Qur’an - Palufi, Ayi Nutfi; Syahid, Ahmad (CV. Creative Tugu Pena, 2020)
The problem found when the children did not read Al Quran fluently. The aim of this study is to provision of the students’ voluble reading Al Quran. It was qualitative research that consist of 20 students at PPTQ Assalam Bandung City. The sample of this research was 20 students in 12 – 15 years old. The result showed that through Yanbu’a methods in application of reading Al Quran, the students was enthusiastic and fluent reading. They got easier in understanding of Tajwid in reading Al Quran Keywords: Yanbu’a Method, Reading Al Quran